Revolutionizing Silage Production Process: Enhancing Quality with Expired Commercial Syrup Addition in Fresh Silage made of Napier Grass and Fine Rice Bran - Sadarman, Sadarman; Febrina, Dewi; Saleh, Eniza; Fazly, Mhd; Prastyo, Agustin Bayu; Qomariyah, Novia; Azmi, Amirul Faiz Mohd (JURNAL ILMIAH PETERNAKAN TERPADU, 2024)
This study aims to evaluate the effect of the addition of expired commercial syrup as an additive to the silage characteristics of a mixture of dwarf elephant grass and fine rice bran. This research was conducted at the Nutrition and Feed Technology Laboratory, Faculty of Agriculture and Animal Science, Universitas Islam Negeri Sultan Syarif Kasim Riau. The content of Water-Soluble Carbohydrates (WSC), ammonia, and total VFA were tested at the Dairy Cattle Laboratory, Faculty of Animal Science, IPB University. A completely randomized design with 5 treatments and 5 replicates was used in this experiment. The treatment distribution was as follows: P1: Odot Grass + Fine Rice Bran 5% DM (control), while P2, P3, P4, and P5 were the addition of expired commercial syrup as much as 2.50%, 5%, 7.50%, and 10% DM, respectively. The ensilage process lasted for 30 days at room temperature. Parameters measured included pH, WSC, ammonia, total VFA, and dry matter loss. Data were analyzed using analysis of variance, further tested using DMRT at 5% significance level. The results showed that the addition of expired commercial syrup up to 10% DM had a significant effect (P<0.05) on increasing lactic acid production so as to lower the pH towards acidic and reduce ammonia content, but there was variation in total VFA between treatments, including dry matter loss which was not significantly different between treatments supplemented with expired commercial syrup. In conclusion, expired commercial syrup can be used at 5% DM to reduce ammonia and increase total VFA of silage made from dwarf elephant grass and fine rice bran.